Prevalence and characterisation of potentially virulent Vibrio parahaemolyticus in seafoods in Malaysia using conventional methods, PCR and REP-PCR - Paydar, M.; Teh, C.S.J.; Thong, Kwai Lin (Elsevier, 2013)
A previously developed multiplex PCR targeting gyrB of Vibrios at genus level and pntA genes for specific detection of Vibrio cholerae, Vibrio parahaemolyticus and Vibrio vulnificus was evaluated. The sensitivity of the multiplex PCR on spiked seafood was 1.5 × 103 CFU g−1. One hundred and fifty seafood samples were collected from retail stores and hypermarkets in different locations in Kuala Lumpur, Petaling Jaya and Seri Kembangan. The prevalence of V. parahaemolyticus was 29% (43/150). The pntA primers for V. parahaemolyticus detection were 100% specific and comparable to the toxR gene-based PCR. Six (12%) and 2 (4%) isolates contained trh and tdh genes, respectively. Repetitive Extragenic Palindromic PCR (REP-PCR) was used to genetically characterize the V. parahaemolyticus isolates in which 41 REP profiles were observed and all the isolates were categorized into 11 distinct clusters at the similarity of 80%. tdh-positive isolates shared a low level of similarity with trh-positive isolates. The prevalence of V. parahaemolyticus and particularly the presence of virulent gene such as trh and tdh among the isolates reiterate a high risk of contamination for seafood consumers in Malaysia. DNA fingerprinting of V. parahaemolyticus in this study indicates a high genetic diversity among the isolates and REP-PCR was able to distinguish the isolates with different virulotypes.